2017
DOI: 10.18203/2394-6040.ijcmph20171365
|View full text |Cite
|
Sign up to set email alerts
|

A community based cross sectional study to estimate total cardiovascular risk in rural Punjab

Abstract: Background: Cardiovascular diseases (CVD) are leading cause of non communicable deaths in India. CVD risk prediction charts by World Health Organization/International Society of Hypertension (WHO/ISH) are designed for implementing timely preventive measures. The objective of the study was to assess the prevalence of CVD risk parameters and to estimate total CVD risk among adults aged ≥40 years, using the WHO/ISH risk charts alone and also to assess the effect of the inclusion of additional criteria on CVD risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Our study found an alarmingly high prevalence of hypertension, with more than half of the women having hypertension and one-third in the pre-hypertensive phase. Similarly high proportion of hypertension among women aged 40–70 years has been described in studies in Ludhiana (53.4%)[ 8 ] and Fatehgarh Sahib (70%)[ 25 ] in Punjab and in slums of Kolkatta (51.8%). [ 26 ] This finding indicates an opportunity for action, as reduction in blood pressure significantly lowers CVD risk.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our study found an alarmingly high prevalence of hypertension, with more than half of the women having hypertension and one-third in the pre-hypertensive phase. Similarly high proportion of hypertension among women aged 40–70 years has been described in studies in Ludhiana (53.4%)[ 8 ] and Fatehgarh Sahib (70%)[ 25 ] in Punjab and in slums of Kolkatta (51.8%). [ 26 ] This finding indicates an opportunity for action, as reduction in blood pressure significantly lowers CVD risk.…”
Section: Discussionsupporting
confidence: 64%
“…Our study found that more than one in ten women had a high risk of CVD, that is ≥20% chance of a cardiovascular event occurring within the next 10 years, which was aligned with the finding of a study in rural Ludhiana, where 15.3% of the women had high CVD risk. [ 8 ] However, a lower proportion was seen in two studies in Tamil Nadu. One in Salem, among women aged 40–70 years which found 6.5% high CVD risk[ 15 ] and the other in a village near Chennai among both men and women, where 6.25% had high CVD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In contrast a study conducted in rural Punjab to estimate cardiovascular risk by Vikramaditya et al reported 19.1% of the study population having moderate risk(10-20%) and 16% of the population having high risk (>20%) using WHO/ISH risk prediction chart. 7 Out of total medium and high CVD risk individuals, 56.36% were males. This may be due to higher prevalence of smoking (15.3%) in males.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast a study conducted in rural Punjab to estimate cardiovascular risk by Vikramaditya et al, reported 19.1% of the study population having moderate risk (10-20%) and 16% of the population having high risk (>20%) using WHO/ISH risk prediction chart. 7 Another study at Mongolia, Malaysia and Cambodia, reveals prevalence of "high CVD risk" (≥20% chance of developing a cardiovascular event over 10 years) was 6%, 2.3% and 1.3% respectively. Of those at "moderate risk" (10≤20% chance of developing a cardio vascular event over 10 years), 100%, 94.3% and 30.1%, respectively are affected by at least one risk-increasing factor.…”
Section: Resultsmentioning
confidence: 99%